2020
DOI: 10.1101/2020.07.28.225847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolism of glucose and glutamine is critical for skeletal muscle stem cell activation

Abstract: Injury to muscle tissue induces the resident, quiescent, skeletal muscle stem cells (MuSCs) to activate - to exit quiescence and enter the cell cycle. Previous work has shown that MuSC activation is associated with significant metabolic changes, however the substrates that MuSCs consume to support activation are poorly understood. Here, we show that MuSCs generate the majority of their energy through mitochondrial respiration, and that oxidative phosphorylation is required for MuSC activation. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The critical role of glutamine in stimulating PASK nuclear translocation prompted us to examine the role of glutamine metabolism in various stages of self-renewal and differentiation. As expected, based on previous reports (Ahsan et al, 2020; Shang et al ., 2020), glutamine withdrawal in cultured myoblasts significantly reduced proliferation (Figure 5A). The glutamine withdrawn cells were significantly enlarged and remained alive in cell culture for at least 4 days (Figure 5A).…”
Section: Resultssupporting
confidence: 91%
“…The critical role of glutamine in stimulating PASK nuclear translocation prompted us to examine the role of glutamine metabolism in various stages of self-renewal and differentiation. As expected, based on previous reports (Ahsan et al, 2020; Shang et al ., 2020), glutamine withdrawal in cultured myoblasts significantly reduced proliferation (Figure 5A). The glutamine withdrawn cells were significantly enlarged and remained alive in cell culture for at least 4 days (Figure 5A).…”
Section: Resultssupporting
confidence: 91%
“…Finally, myoblasts turn on the 80 transcription factor myogenin (MyoG), a marker of terminal differentiation, and exit the cell cycle 81 to fuse into myotubes. Previous studies have shown that the glucose promotes activation of 82 quiescent muscle stem cells and differentiation of myoblasts in part by regulating histone acetylation , Yucel et al, 2019, Ahsan et al, 2020, Theret et al, 2017. In differentiated myotubes, glucose inhibits the Foxo transcription factors whose activity induces the 85 expression of muscle-specific ubiquitin ligases that result in atrophy (Sandri et al, 2004, Meng et (which was not certified by peer review) is the author/funder.…”
Section: Introduction 56mentioning
confidence: 99%